Analisis Urgensi Pendidikan Akhlak Berkarakter Dalam Membangun Keluarga Bahagia - Annisa Fitri Dewianti; Farhah Desrianty Gimri; Elsa Marfina Nandiani; Bambang Ardiansyah; Wismanto Wismanto (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This article aims to explain how important moral education is starting from within the family where parents play a major role in educating children and are responsible for the development of their souls and beliefs. The method of writing in this article is carried out by the library research method. From the results of this study it can be concluded that happiness and well-being are not always related to one's success in reaching the peak or sufficient material, but can be obtained through the appreciation and practice of religious teachings. Therefore, humans are required to prepare themselves and family experts with religious education as the basic capital in carrying out life in this world and provisions for the hereafter. One of the main things is religious education which must be learned from an early age, because the teachings of Islam must be the foundation or guidance in the subsequent development of the child's soul.